Evaluation of the Publication Distribution Service Dora: case study Nigeria - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The purpose for which CTA commissioned this study is to determine DORA’s impact on the performance of beneficiaries (teachers, students, and participating institutions) so as to facilitate necessary improvement...